Optimizing Digital Financial Inclusion to Achieve SDGs through Accelerating Womenpreneurs as Economic Empowerment - Lailiyah, Elliv Hidayatul; Fajri, Mega Barokatul (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
The purpose of this study is to analyze and formulate strategies to optimize financial inclusion through womenpreneurs, because womenpreneurs can be economic empowerment so that the 2030 SDGs target can be achieved. Womenpreneurs can be actors who contribute significantly to economic development. However, womenpreneurs have a low financial inclusion index which will hinder the achievement of the SDGs target in 2030. This study uses a qualitative method with a case study approach to explore and obtain empirical evidence about strategies in optimizing digital financial inclusion in womenpreneurs. The subjects of this study were womenpreneurs from the Aisyiyah women's MSMEs group in Lamongan Regency, the head of regional leader of aisyiyah (PDA), the head of the cooperative and micro business office of Lamongan Regency and the head of the Industry and Trade office of Lamongan Regency. Data collection used interview and observation methods. Data analysis was carried out by means of data reduction, presentation of data conclusions and data verification. After the key data has been determined, the next step is to conduct an analysis using SWOT analysis and PEST analysis to formulate the strategy. There are two strategies formulated, first SOT Strategy provides full power, increases opportunities, and eliminates threats. Second, WOT Strategy fixes weaknesses, takes advantage of opportunities, and holds back threats.